Production and characterization of dried-salted juvenile hybrid tilapia - Jamelarin, Virginia Bergemann (2005.)
Thirty (30) day-old juvenile pond-cultured sex-reversed male Oreochromis mossambicus-niloticus, a hybrid tilapia, was salted in saturated brine at a shade temperature range of approximately 21.1 degree celcius to 26.7 degree celcius and sun-dried in direct sunlight for total of 11 hours with an average atmospheric relative humidity (RH) exposure of 55.1%, values ranging from 34% RH to 72% RH, and a mean temperature exposure of 34.9 degree C, ranging from 27.2 degree C to 43.3 degree C.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Tilapia; Salted fish